Philosophy and Psychiatry - Delgado, Honorio (1959)
Undoubtedly one of the characteristics of current psychiatry is a tendency to extend its scope in all directions. So no wonder that philosophical ideas are incorporated into the study of mental disorders in the prosecution of the biography of the patient, discussion of problems relating to the interaction of the organic functions with the psychic in psychotherapeutic work and in the examination of the psychiatric knowledge.